2022
DOI: 10.3390/min12020165
|View full text |Cite
|
Sign up to set email alerts
|

Neptunium and Uranium Interactions with Environmentally and Industrially Relevant Iron Minerals

Abstract: Neptunium (237Np) is an important radionuclide in the nuclear fuel cycle in areas such as effluent treatment and the geodisposal of radioactive waste. Due to neptunium’s redox sensitivity and its tendency to adsorb strongly to mineral phases, such as iron oxides/sulfides, the environmental mobility of Np can be altered significantly by a wide variety of chemical processes. Here, Np interactions with key iron minerals, ferrihydrite (Fe5O8H·4H2O), goethite (α-FeOOH), and mackinawite (FeS), are investigated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 69 publications
(139 reference statements)
0
4
0
Order By: Relevance
“…Sulfidation of iron (oxyhydr)­oxides is a complex multi-step process, which typically results in reductive dissolution at the mineral surface, forming elemental sulfur (S 8 0 ) and releasing Fe­(II) into solution. , The resultant aqueous Fe­(II) may then react with aqueous HS – to form secondary iron sulfide phases, such as mackinawite (FeS). , Aqueous HS – may also react with S 8 0 to form surface-associated polysulfide (S n 2– ) species . Consequently, these complex processes may influence the behavior and fate of radionuclides, including U. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sulfidation of iron (oxyhydr)­oxides is a complex multi-step process, which typically results in reductive dissolution at the mineral surface, forming elemental sulfur (S 8 0 ) and releasing Fe­(II) into solution. , The resultant aqueous Fe­(II) may then react with aqueous HS – to form secondary iron sulfide phases, such as mackinawite (FeS). , Aqueous HS – may also react with S 8 0 to form surface-associated polysulfide (S n 2– ) species . Consequently, these complex processes may influence the behavior and fate of radionuclides, including U. , …”
Section: Introductionmentioning
confidence: 99%
“… 46 Consequently, these complex processes may influence the behavior and fate of radionuclides, including U. 26 , 47 50 …”
Section: Introductionmentioning
confidence: 99%
“…The mechanism by which actinides are sequestered during Fh formation is unknown and of significant interest. 2–4…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism by which actinides are sequestered during Fh formation is unknown and of significant interest. [2][3][4] Studies have shown that Fh formation can potentially occur through several competing pathways. One proposed route proceeds via polymerisation of small molecular Fe(III) species such as dimers and trimers.…”
Section: Introductionmentioning
confidence: 99%